Pengaruh Waktu Paparan Zat Pengatur Tumbuh Terhadap Tingkat Abnormalitas Klon Kelapa Sawit - Dian Rahma Pratiwi; Sri Wening; Erwin Nazri (Jurnal Penelitian Kelapa Sawit, 2020)
One of components frequently found in plant culture media is plant growth regulator (PGR), which is needed to stimulate plant culture growth. Excessive PGR addition can induce clone abnormality. It is needed comprehensive study to understand the effect of time exposure of PGR to oil palm clone abnormality in the field. This research aims to study the effect of total exposure time of PGR as well as exposure time of each medium containing different PGRs to abnormality rate of oil palm clones in the field. Four lines of oil palm clones with aged 4 years (P,Q, R, and S) were used for tracking the incubation time in the laboratory and abnormality rate in the field. The relation between variables was analyzed by using correlation, multiple linear regression and simple linear regression analysis. The results showed that length of PGRs exposure time significantly affected the clone abnormality in the field. Longer the exposure time (more than 171 days), higher the abnormality rate. From the three media containing PGR, medium containing 2,4-D and 2,4,5-TCPP significantly affected and had high significant positive correlation to clone abnormality than medium containing 2,4-D and BAP. Medium containing NAA did not show any correlation with clone abnormality rate. On the contrary, the results showed that length of incubation time in media without any PGR did not affect rate of abnormality significantly and it also had negative correlation. Linear model can be used to estimate the clone abnormality rate in the field, based on exposure time of PGR during the in vitro process.